PENGEMBANGAN E-LAPD INKUIRI BERBASIS STEM UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MATERI LAJU REAKSI - Mulyasari, Yanti; Hidayah, Rusly (UIN AR-RANIRY, 2026)
Critical thinking is an essential component of higher-order thinking skills that plays a crucial role in addressing the challenges of the twenty-first century. This study aimed to develop a STEM-based inquiry Electronic Student Activity Worksheet (E-LAPD) on the topic of reaction rates to enhance students' critical thinking skills. The study employed a Research and Development (R&D) approach using the 4D development model, which was limited to the Develop stage. A limited trial was conducted with 36 eleventh-grade students at SMA Negeri 1 Menganti using a One-Group Pretest–Posttest design. The results showed that the E-LAPD achieved a mode score of 4 for both content and construct validity. Its practicality was demonstrated by the students' activity implementation rate of 98.5% and a student response rate of 98.6%. Its effectiveness was indicated by an N-gain score of 0.80, which falls into the high category, suggesting an improvement in students' critical thinking skills. Therefore, the STEM-based inquiry E-LAPD met the criteria of validity, practicality, and effectiveness and is suitable for use in reaction rate instruction to enhance students' critical thinking skills.